THE DURABILITY OF HYGRO-IMMERSION AGED CELLULOSE FIBRE REINFORCED POLYMER LAYERED SILICATE NANOCOMPOSITES - Kowshik, C. S. Suhas; Mohan, Nanjangud; Naik, Nithesh; Shettar, Manjunath; Bhat, Ritesh; Rohatgi, Shivaksh (IIUM Engineering Journal, 2020)
This study aims at investigating the effect of water ageing on the durability of cellulose fibre reinforced polymer layered silicate nanocomposite. The material used comprises cellulose fibres from pinewood as reinforcement and high-density polyethene (HDPE) coupled with nanoclay as matrix phase. The prepared material is subjected to tap water ageing for 21 days. The durability is quantified by Barcol hardness for the material and measured at an interval period of 7 days. The obtained results indicate a reduction of hardness by 5.24, 13.17, and 16.60% in 7, 14, and 21 days aged nanocomposites. Besides, the one-way ANOVA test shows that the immersion time for the composite has a significant effect on the durability of the material with an R2 value of 99.96% tested at 95% confidence interval. The concluding remarks are validated using the results obtained for thickness swelling using the Fourier analysis. The work also presents a regression equation with high degree of accuracy, capable of estimating the Barcol hardness value for a given immersion time. ABSTRAK: Kajian ini bertujuan untuk mengkaji kesan penuaan air terhadap ketahanan nanokomposit silikat berlapis polimer bertetulang serat selulosa. Bahan yang digunakan terdiri daripada serat selulosa dari kayu pina sebagai tetulang dan polietena berketumpatan tinggi (HDPE) ditambah dengan nanoclay sebagai fasa matriks. Bahan yang disediakan mengalami penuaan air paip selama 21 hari. Ketahanan diukur dengan kekerasan bahan Barcol dan diukur pada selang waktu 7 hari. Hasil yang diperoleh menunjukkan penurunan kekerasan sebanyak 4.74, 8.88 dan 18.90% dalam nanokomposit usia 7, 14 dan 21 hari. Selain itu, analisis satu arah ujian varians menunjukkan bahawa masa rendaman komposit mempunyai pengaruh yang signifikan terhadap ketahanan bahan dengan nilai R2 99.96% yang diuji pada selang keyakinan 95%. Ucapan penutup disahkan menggunakan hasil yang diperoleh untuk pembengkakan ketebalan menggunakan analisis Fourier. Karya ini juga menyajikan persamaan regresi dengan tahap ketepatan yang tinggi, yang dapat menganggarkan nilai kekerasan Barcol untuk masa rendaman tertentu.